Sistem Deteksi Masker Menggunakan Algoritma Haar Cascade dalam Menghadapi Era New Normal - Rudi Suhirja; Jemakmun Jemakmun (LPPM STIKI MALANG, 2022)
The covid-19 outbreak originated from a cluster of human pneumonia cases in the Chinese city of Wuhan in late December 2019. Covid-19 has been an outbreak in Indonesia since March 2020. Not only in our country, but the spread of the covid-19 virus has also affected every country in the world. Therefore, currently, various places have implemented special rules to comply with health protocols. One of them is the 2020 governor's (pub) government, where all southern Sumatra must follow health protocols by wearing masks. This mask detection system program is a way to overcome public awareness, especially among students at Bina Darma University, that how important the use of masks is today. by utilizing artificial intelligence the author created a system to detect masks. In writing this program, the author used python and used the haar cascade algorithm. This haar cascade algorithm was the brainchild of Paul Viola and Michael Jones in 2001, they presented a paper called